Análisis de las campañas de lectura y sus estrategias de comunicación en instituciones de Loja en el año 2017. Casos de estudio: escuelas municipales, ministerio de educación y casa de la cultura núcleo de Loja. - Torres Carrion, Lady Katherine (2019)
This research was created with the purpose of analyzing what communication strategies are used in the campaigns of defense of the institutions such as the house of the core culture of Loja, Ministry of education and municipal schools; This work was a process of search, collection, observation and analysis of the communicative strategies of reading in 2017 in the city of Loja, considering what strategies were applied in these campaigns and what was its relationship with the citizenry. We investigated about reading campaigns, to carry out have how been broadcast in other countries and how they have achieved that the public has a better understanding of them. The research work was encouraged with the application of qualitative method, as a result of her three techniques used or tools such as the application of analysis of content, interviews and focus groups, for the collection of information. The interviews were applied to the authorities responsible for campaigns. Through this methodological technique is managed to verify what was its communicative impact to citizenship thus fulfilling one of the main objectives, also demonstrating the influence had to generate empathy with the Loja community. From these results was a proposal that will contribute to the strengthening of communicative processes of reading in the Loja youth campaigns.